Preparation and Investigation of Some New Pyrazole Derivatives as Corrosion Inhibitors for Mild Steel in Acidic Media. - Khudhair, Zahraa Talib; Shihab, Mehdi Salih (Al-Nahrain Journal of Science, 2018)
Preparation of some new pyrazole derivatives by using a few steps starting from 4-acetylaniline to prepare azo compound (3). Chalcone derivatives (A1-A3) were obtained by reaction compound (3) with a proper aldehyde(benzaldehyde,4-(N,N-dimethylamino) benzaldehyde, terephalaldehyde). Chalcone derivatives (A1-A3) reacted with a proper hydrazine (hydrazine hydrate, phenyl hydrazine) to yield pyrazole derivatives (B1, B2, B3, B4, B5, B6). All prepared structure compounds were confirmed using spectroscopic and1H-NMR techniques. Prepared compounds (B1, B2, B3, B4, B5, B6) were successfully applied as organic corrosion inhibitors for mild steel in 1M H2SO4 solution at 30oC by using a weight loss method. The results of weight loss measurements showed that corrosion inhibition efficiency by increasing the concentration of organic inhibitors for mild steel in 1M H2SO4 solution at 30oC.